(untitled) (African Multidisciplinary Journal of Research, 2025)
Morality and ethics are imperative for sustainable development. Without morality and ethics, children grow up into adults who have no values. Such immoral adults lead institutions and such institutions that are supposed to contribute towards development become malfunctional. If our institutions that are supposed to contribute towards development malfunction and the situation is not curbed in time, future generations will have nothing to inherit. Correction of the pattern is imperative. The objective of this paper is to explicate the moral paradox in the society and elucidate the centrality of morality and ethics in sustainable development. This will be made clear by an explication of Sustainable Development Goals. Sustainable Development Goals are a global call to action to end poverty, protect the earth’s environment and climate change. The call to action for Sustainable Development aims at ensuring that people everywhere can enjoy peace and prosperity. This research entails a review of archival and multimedia sources. The article approaches the discussion from Charles Nyamiti’s African Christology as a model that can influence change of character. In the African Christology as espoused by Nyamiti, Jesus Christ as the ancestor of humankind, and the foundation of existence and reality continuously seeks to achieve social and economic progress in ways which will not exhaust the Earth’s finite natural resources.